Hybrid 4‐Aminoquinoline‐1, 3, 5‐triazine Derivatives: Design, Synthesis, Characterization, and Antibacterial Evaluation. (20th June 2014) - Pathak, P.; Thakur, A.; Bhat, H. R.; Singh, U. P.
<x xml:space="preserve">Abstract</x> A series of novel 4‐aminoquinoline 1, 3, 5‐triazine derivatives were synthesized and characterized by FTIR, 1H‐NMR, 13C‐NMR, MS, and elemental analysis. The antibacterial activities of synthesized compounds were tested against three Gram‐positive bacteria, namely Bacillus subtilis (NCIM‐2063), Bacillus cereus (NCIM‐2156), and Staphylococcus aureus (NCIM‐2079), and four Gram‐negative bacteria, namely Proteus vulgaris (NCIM‐2027), Proteus mirabilis (NCIM‐2241), Escherichia coli (NCIM‐2065), and Pseudomonas aeruginosa (NCIM‐2036), using ciprofloxacin as reference standard drug. Results showed compound 9a and 9e as potent antibacterial agents against all bacterial strains except Bacillus cereus (NCIM‐2156). Copyright © 2014 HeteroCorporation